Mudanças na legislação de trânsito provocam alteração no perfil dos acidentes de trânsito ? uma análise de gênero e frequência semanal no Estado do Piauí de 2001 A 2008 - Barbosa, Elisabeth Lira Leite (2010)
It is aimed to analyse if the “Dry Law” affected the profile of the accidents with victims, in the State of the Piauí. From the base of data extracted of the annual reports of the DETRAN, one intends to check if there were differences behaviours in the proportion of accidents for (feminine) type, and in the proportion of accidents that take place in the ends of week during the period from 2001 to 2008 in the Piauí. For that, they use models of analyses of intervention, where the impacts tell to themselves to variations realized on the averages storms of the studied variables, in models univariates autoregressions. It ends that the coefficients of the variables of changes in the legislation were not statistically significant, what it suggests that the profile of the accidents was not affected.